The Effect Of Student Self-Efficacy On Arabic Learning Achievement At Senior High School/ تأثير الكفاءة الذاتية على التحصيل الدراسي لدى طلبة المدرسة الثانوية - Alfian, Muhammad Ivan; Masykur, Muhammad Zakki; Huda, Miftahul; Khotimah, Nadiah Husnul (Ijaz Arabi Journal of Arabic Learning, 2025)
This study aims to find out (1) how the self-efficacy of students in learning achievements in Arabic, (2) how the achievement of learning Arabic students, and (3) how student self-efficacy affects learning achievement. This study uses a quantitative approach with data collection techniques in the form of questionnaires and tests. This study's subjects were senior high school students XI MA Ihyaul Ulum Pati. The data analysis method in this study is simple linear regression, which looks at the effect through the t-test. The results of this study indicate that (1) Students' self-efficacy towards Arabic learning achievement is in the medium category, (2) Arabic learning achievement is in the moderate category, and (3) There is a positive effect of self-efficacy on student achievement by looking at the calculation results. The t-count value was obtained at 8.889 from the t-table of 1.987 or a significance level of 0.000 0.05, which means Ho is rejected, and Ha is accepted.